PENGARUH INDEPENDENSI, KOMPETENSI, DPC, AKUNTABILITAS, OBJEKTIVITAS, DAN ETIKA PROFESI TERHADAP KUALITAS AUDIT - Zainiah, Miftakhur Rizqi; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to find out the influence of independency, competency, due professional care, accountability, objectivity, and profession ethics to the audit quality. The respondent is auditor staff with the job title junior, senior and supervisor who have been working at Public Accountant Firm in Surabaya. The samples are 10 Public Accountant Firms which have been represented by 32 auditor staffs, these auditor staffs have been obtained by using simple random sampling method. The data has been obtained by issuing questionnaires which have been directly issued to the respondents in the beginning of December 2016. The analysis technique has been carried out by using multiple linear regressions analysis. The results of this research have proven that: (a) independency gives positive influence to the audit quality, it means that when an auditors is independent so that his or her audit quality is getting better; (b) competency does not give any positive influence, it means when the competency of an auditors is getting better, the audit quality is getting better as well; (e) objectivity gives negative influence to the audit quality, it means that the auditor cannot be stated has a good quality if he or she cannot act objectively based on the authentic evidence from the existing facts; It is suggested for the following research to add more variables, to conduct deeper observation, such as interview method and wider of population.Keywords: Independency, competency, accountability, audit quality.